Spatial Land Suitability for Paddy Cultivation: Empirical Analysis of Its Impact on Export Volume and Exchange Rates Behavior in Indonesia - Safrina, Nikma Fista; Rahadi, Raden Aswin (International Journal of Economics Development Research (IJEDR), 2025)
This study explores the linkages between geographical land suitability for rice cultivation and fluctuations in the Rupiah to US Dollar (IDR/USD) exchange rate in Indonesia's macroeconomic context. Combining qualitative and quantitative approaches, the study involved stakeholder interviews and regression analysis of national economic time series data from 1994 to 2024. Spatial analysis using the Multi-Criteria Decision Analysis (MCDA) approach was used to assess land suitability, considering legal restrictions on conversion of paddy fields and conservation forests. Results show that land suitability-based rice production has a statistically significant effect on exchange rate at the 10% level (p = 0.0883), with a positive coefficient of 0.0499, indicating that increased production is associated with Rupiah depreciation. In contrast, GRDP shows a significant negative effect on the exchange rate (p < 0.05), indicating its contribution to currency appreciation. Mediation analysis revealed that although rice production significantly increased export volume (p = 0.0053), the relationship between export and exchange rate did not prove significant (p = 0.3962). This suggests that increased production does not automatically strengthen the exchange rate without effective integration into the trading system. The qualitative interviews highlighted the importance of adaptive strategies by stakeholders in food security management. The findings emphasize the need for synchronization between agricultural expansion policies and macroeconomic strategies to sustainably achieve exchange rate stability and national food security.